Meeting the needs of cancer patients: identifying patients’, relatives’ and professionals’ representations - Foà, Chiara; Copelli, Patrizia; Cornelli, Maria Cristina; De Vincenzi, Franca; Fanfoni, Rita; Ghirardi, Lida; Prandi, Rossella; Artioli, Giovanna; Mancini, Tiziana (Acta Biomedica Atenei Parmensis, 2014)
Background and aim: The literature on cancer patients agrees that most of the cancer patients’ needs often remain unmet. How are these different needs perceived by patients, relatives and professionals? The present research has tried to make a contribution by analysing evidences of the needs, especially unmet, that different actors attribute to a cancer patient. Method: A total of 42 Italian participants (76.2% women) took part in the study. Patients, relatives, physicians, nurses, social care assistants and volunteers participated separately in six focus groups. Three face-to-face interviews were conducted with psychologist, general practitioner and social worker. All focus groups/interviews were processed through an analysis of thematic content. Results: The results showed a priority given to the need for information, and also the importance of psychological and social support needs, confirming that they remain unmet. Differences between participants are visible by looking at the needs cited more frequently. For example, the oncologists are more sensitive to information needs related to the illness and its treatment, while the social worker cited the need for social, economic and legal assistance more frequently. The nurses highlighted the need for continuity of care, and the psychologists underlined the importance of psychological support, while the relatives cited the need of support both from and for families. Conclusions: Results suggested that a comprehensive approach that addresses medical and psychosocial factors is needed. Cancer patients must be provided with a multidisciplinary survivorship care plan that addresses information related to their long-term care and identifies available psychological and social services.